1981
DOI: 10.1104/pp.67.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Response of Tomato Plants to Stressful Temperatures

Abstract: To investigate the abscisic acid (ABA) production of tomato (Mill.) plants in response to diurnal stressful temperatures, five-week old seedlings were exposed to day/night temperatures of 10/5, 15/10, 25/15, 35/25, or 45/35 C. The daylength was 16 hours with a light intensity of approximately 400 microeinsteins per meter per second. Plant tops were sampled at 12, 24, 48, and 72 hours. Free, alkaline-hydrolyzable (conjugated), and total ABA quantities were measured using standard gas chromatographic techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
61
0
2

Year Published

1984
1984
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 9 publications
6
61
0
2
Order By: Relevance
“…Another interesting aspect to take into account is the photosynthetic capacity of the plant. It has been reported in literature that ABA stops the photosynthesis of different species under controlled conditions (Daie & Campbell, 1981;Xu et al, 1995;Gong et al, 1998;Wilkinson & Davies, 2002;Reddy et al, 2004;Liu et al, 2005); but our results showed an increase in the content of dry matter that increases in correlation with chlorophyll levels (Travaglia et al, 2009). These results are similar to those we observed during three years of essays with field-grown wheat treated with ABA; the treated plants showed higher levels of chlorophyll and maintained green leaves longer (5 to 10 days) than control plants (Travaglia et al, 2010).…”
Section: Aba Promotes Yield In Field-cultured Soybeansupporting
confidence: 81%
“…Another interesting aspect to take into account is the photosynthetic capacity of the plant. It has been reported in literature that ABA stops the photosynthesis of different species under controlled conditions (Daie & Campbell, 1981;Xu et al, 1995;Gong et al, 1998;Wilkinson & Davies, 2002;Reddy et al, 2004;Liu et al, 2005); but our results showed an increase in the content of dry matter that increases in correlation with chlorophyll levels (Travaglia et al, 2009). These results are similar to those we observed during three years of essays with field-grown wheat treated with ABA; the treated plants showed higher levels of chlorophyll and maintained green leaves longer (5 to 10 days) than control plants (Travaglia et al, 2010).…”
Section: Aba Promotes Yield In Field-cultured Soybeansupporting
confidence: 81%
“…Endogenous levels of ABA have been shown to increase during high and low temperature growth conditions (8). Following application of exogenous ABA, improved cold resistance has been observed in alfalfa seedlings (22), potatoes (5), and suspension cultures of some plant species (4,19) and callus cultures (14).…”
mentioning
confidence: 99%
“…The greatest increase in ABA concentration has been observed in response to drought stress, yet other osmotic stresses such as salinity and PEG-mediated water deficit also result in elevated levels of ABA ( 19). Temperature also has an effect on endogenous ABA levels (8). However, the effect of a rapid increase in temperature or heat shock on leaf ABA concentration has not been widely studied (13).…”
mentioning
confidence: 99%